The Effectiveness of the RADEC Learning Model in Strengthening Religious Character and Critical Thinking among Elementary School Students - Nana Suryana; Wahyu Sopandi; Yadi Ruyadi (Jurnal Penelitian Pendidikan IPA, 2026)
This research is based on the persistently low critical thinking skills of students and the suboptimal internalization of religious character values in the learning process in elementary schools. Learning that is still oriented toward memorization and teacher-centered approaches results in students being less engaged in reflective, dialogical, and contextual activities. However, the demands of 21st-century education and the Pancasila Student Profile emphasize the importance of strengthening religious character and critical reasoning skills in an integrated manner starting from elementary school. This study aims to analyze the effectiveness of the RADEC learning model in strengthening religious character and critical thinking skills in elementary school students. This study used a quantitative approach with a one-group pretest-posttest design. The subjects were 125 elementary school students in Cluster IV, Pagerageung District, Tasikmalaya Regency. The RADEC learning model was implemented in the learning process using the syntax "Read, Answer, Discuss, Explain, and Create," which was designed to encourage literacy activities, critical discussions, value reflection, and actualization of student understanding. The research instruments were a religious character questionnaire and a critical thinking questionnaire, both of which have been tested for validity and reliability. Data were collected through measurements before and after the implementation of the RADEC learning model. Data analysis was conducted using descriptive statistics and the Wilcoxon Signed Rank Test to determine differences in students' religious character scores and critical thinking skills before and after the treatment. The results showed that the RADEC learning model was significantly effective in strengthening students' religious character with a significant value of p < 0.05. Furthermore, students' critical thinking skills also significantly improved after participating in the RADEC learning model. The findings of this study indicate that the RADEC learning model is effective as an alternative learning method in elementary schools to improve students' religious character and critical thinking skills. Practically, the RADEC model can support learning that is more meaningful and relevant to students' needs. Empirically, this study provides evidence that literacy-based learning, discussion, and reflection can simultaneously strengthen character education and higher-order thinking skills.